Combining bleach and mild predigestion improves ancient DNA recovery from bones. (15th December 2016) - Boessenkool, Sanne; Hanghøj, Kristian; Nistelberger, Heidi M.; Der Sarkissian, Clio; Gondek, Agata T.; Orlando, Ludovic; Barrett, James H.; Star, Bastiaan
Abstract: The feasibility of genome‐scale studies from archaeological material remains critically dependent on the ability to access endogenous, authentic DNA. In the majority of cases, this represents a few per cent of the DNA extract, at most. A number of specific pre‐extraction protocols for bone powder aimed to improve ancient DNA recovery before library amplification have recently been developed. Here, we test the effects of combining two of such protocols, a bleach wash and a predigestion step, on 12 bone samples of Atlantic cod and domestic horse aged 750–1350 cal. years before present. Using high‐throughput sequencing, we show that combined together, bleach wash and predigestion consistently yield DNA libraries with higher endogenous content than either of these methods alone. Additionally, the molecular complexity of these libraries is improved and endogenous DNA templates show larger size distributions. Other library characteristics, such as DNA damage profiles or the composition of microbial communities, are little affected by the pre‐extraction protocols. Application of the combined protocol presented in this study will facilitate the genetic analysis of an increasing number of ancient remains and will reduce the cost of whole‐genome sequencing.